Kinematic of symmetric deployable scissor-hinge structures with integral mechanism mode. (15th October 2017) - Chen, Yao; Fan, Linzi; Feng, Jian
Highlights: Concept of integral mechanism mode is presented. Integral mechanism mode preserves full symmetry. Improved kinematic analysis of deployable scissor-hinge structures is performed. Possible interferences among nonadjacent members are concerned. Kinematic singularity along the whole motion path can be efficiently detected. Abstract: Some cases of kinematic behavior of deployable scissor-hinge structures, which consist of link members and pivot and hinge joints, have been investigated. However, few have concerned the inherent symmetry and potential interference of these structures. Here we present a new mode of integral mechanism for symmetric structures. Adopting this integral mechanism mode, the algorithm of kinematic analysis is improved, and is capable of following the motion path of a scissor-hinge structure efficiently. During deployment, the geometric configurations and kinematic indeterminacy of the structure are studied. Further, we concern the interferences among nonadjacent members and potential kinematic singularity for these deployable structures. Numerical analysis points out that kinematic singularity could be induced when a scissor-hinge structure is fully deployed or folded. Geometric transformations of these deployable structures are continuous and significant when moving along the motion path. Nevertheless, the inherent symmetry keeps unchanged, and the integral mechanism mode preserves full symmetry. The proposed integral mechanism mode is unique to a specific deployable structure, and it is therefore helpful for further studies on deployable structures.